Qualitative research and analyses of the economic impacts of cash transfer programmes in Sub-Saharan Africa: A research guide prepared for the From Protection to Production project - Oxford Policy Management (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction] This research guide was prepared as part of the joint FAO-UNICEF `From Protection to Production' (PtoP) project (http://www.fao.org/economic/ptop/en/). The project takes advantage of ongoing impact evaluations of cash transfer programmes in sub-Saharan Africa to look at the impact of these programmes on household economic activities, including labour supply, as well as their impact on the local economy. The project is using a mixed-method approach, combining econometric analysis of impact evaluation data, local economy Social Accounting Matrix (SAM)/computable general equilibrium (CGE) models and qualitative methods. This research guide on qualitative methods provides an overview of the training, fieldwork preparation and research process in each case study country, introduces the participatory tools that will be used to help gather information and provides guidance for conducting key informant interviews and facilitating focus group discussions. It is designed as an easy-to-use overall guide for the research teams in the case study countries and, therefore, minimises the repetition of information which is provided elsewhere (for example, in the Concept Note). The guide is structured as follows: Section 2 lists the key evaluation questions and hypotheses; Section 3 outlines the research process, including the structure for the training workshop; Section 4 explains the overall research methods and approaches; Section 5 provides more detailed question guidelines for each thematic area; Annex A describes how to use the participatory research tools; and Annex B details a proposed training schedule for the national field team. While Sections 2 to 4 apply generically across the case study research countries, the research process in each country will contextualise and nuance the question guidelines in Section 5 to suit the programme context in that country.
Keywords: 330